gas-tight shock tube apparatus for laboratory volcanic lightning under varying atmospheric conditions - Christina Springsklee; Bettina Scheu; Christoph Seifert; Michael Manga; Corrado Cimarelli; Damian Gaudin; Oliver Trapp; Donald B. Dingwell (Volcanica, 2023)
Explosive volcanic eruptions generate electrical discharges, a phenomenon termed volcanic lightning (VL). VL is increasingly well-investigated and monitored for modern eruptions, however volcanism has been active since Earth’s origin. Thus, investigating VL under different atmospheric conditions is relevant for studies of early atmospheric chemistry and potential prebiotic reactions. We developed an experimental setup to investigate VL in varying atmospheres. We present the first experiments of laboratory discharges in particle-laden jets in varying atmospheric conditions. The new experimental setup is a mobile fragmentation bomb erupting into a gas-tight particle collector tank. This setup enables the testing of different atmospheric conditions, changes in the carrier gas of the jet, changes in the pressure within the tank, monitoring of the jet behaviour, and sampling of the atmosphere together with the decompressed solid materials. We find that the number and magnitude of near-vent electrical discharge events are similar in CO2-CO and air atmospheres.